Measurement of the critical resolved shear stress for basal slip in magnesium alloys using instrumented indentation. (November 2018) - Nayyeri, G.; Poole, W.J.; Sinclair, C.W.; Zaefferer, S.
Abstract: The critical resolved shear stress (CRSS) for basal slip for a range of magnesium alloys was determined using instrumented indentation. Good agreement was observed between the analysis from spherical indenters with different radii and literature results from single crystal tests on Mg-Al alloys. In the case of tests on a Mg-1Zn-0.5Nd alloy, the indentation size effect showed a change in behavior for indenters with a radius of <13 μm. The change in behavior was proposed to be related to the activation of second order pyramidal slip which was confirmed by three-dimensional electron backscatter diffraction-based orientation microscopy (3D-EBSD) analysis. Graphical abstract: Unlabelled Image